스마트 컨트랙트 보안 취약점 분석 및 보안 자동화 모델 - 조도은(Do-Eun Cho) (디지털콘텐츠학회논문지, 2024)
스마트 컨트랙트는 블록체인 기술의 핵심 구성요소로 계약 조건이 충족되면 자동으로 시행되기 때문에 디지털 데이터에 대한 신뢰도가 필요한 다양한 분야에서 활용되고 있다. 그러나 스마트 컨트랙트는 여러 보안 취약점과 프라이버시 위협을 가지고 있으므로 이에 대한 보안 강화 방안이 필요하다. 본 연구에서는 스마트 컨트랙트의 동작 과정별 보안 취약점을 분석하고, 각 단계별 보안 자동화 모델을 제시하였다. 스마트 컨트랙트의 보안은 전체 생명 주기에 걸쳐 중요하며, 각 동작 단계에서 수행되어야 할 보안 사항을 자동화한다면 오류를 최소하며, 보안 유지 관리의 부담을 줄일 수 있다. 제안한 보안 자동화 모델의 보안성 분석을 통해 각 단계별 보안 위협에 대한 보안성을 모두 만족하는 것으로 분석하였다. 향후 제안한 모델을 다양한 실제 사례에 적용하여 구현함으로써 블록체인 기술의 보안 및 신뢰성을 강화하고, 광범위한 사용자에게 안전한 블록체인 환경을 제공할 수 있을 것이다. Smart contracts are a key component of blockchain technology and are used in various fields that require reliability for digital data because they are automatically implemented when contract conditions are met. However, smart contracts have several security vulnerabilities and privacy threats; thus, measures to strengthen security are needed. In this paper, security vulnerabilities for each operation process of smart contracts were analyzed, and a security automation model for each step was presented. The security of smart contracts is important throughout its entire life cycle, and automating the security steps to be performed at each operation stage can minimize errors and reduce security maintenance. A security analysis of the proposed security automation model revealed that all security requirements against threats at each stage were satisfied. By applying and implementing the proposed model in the future to various real-world cases, it will be possible to strengthen the security and reliability of blockchain technology and provide a safe blockchain environment to a wide range of users. KCI Citation Count: 1